Disulfides from the Brown Alga Dictyopteris Membranacea Suppress M1 Macrophage Activation by Inducing AKT and Suppressing MAPK/ERK Signaling Pathways - Daskalaki, Maria G. (Mar Drugs, 2020)
Inflammation is part of the organism’s response to deleterious stimuli, such as pathogens, damaged cells, or irritants. Macrophages orchestrate the inflammatory response obtaining different activation phenotypes broadly defined as M1 (pro-inflammatory) or M2 (homeostatic) phenotypes, which contribute to pathogen elimination or disease pathogenesis. The type and magnitude of the response of macrophages are shaped by endogenous and exogenous factors and can be affected by nutrients or therapeutic agents. Multiple studies have shown that natural products possess immunomodulatory properties and that marine algae contain products with such action. We have previously shown that disulfides isolated from Dictyopteris membranacea suppress nitric oxide (NO) production from activated macrophages, suggesting potential anti-inflammatory actions. In this study, we investigated the anti-inflammatory mechanism of action of bis(5-methylthio-3-oxo-undecyl) disulfide (1), 5-methylthio-1-(3-oxo-undecyl) disulfanylundecan-3-one (2) and 3-hexyl-4,5-dithiocycloheptanone (3). Our results showed that all three compounds inhibited M1 activation of macrophages by down regulating the production of pro-inflammatory cytokines TNFα, IL-6 and IL-12, suppressed the expression of the NO converting enzyme iNOS, and enhanced expression of the M2 activation markers Arginase1 and MRC1. Moreover, disulfides 1 and 2 suppressed the expression of glucose transporters GLUT1 and GLUT3, suggesting that compounds 1 and 2 may affect cell metabolism. We showed that this was due to AKT/MAPK/ERK signaling pathway modulation and specifically by elevated AKT phosphorylation and MAPK/ERK signal transduction reduction. Hence, disulfides 1–3 can be considered as potent candidates for the development of novel anti-inflammatory molecules with homeostatic properties.